MRI of middle ear cholesteatoma: The importance of observer reliance from diffusion sequences. Issue 1 (16th August 2021) - Fischer, Natalie; Plaikner, Michaela; Schartinger, Volker H.; Kremser, Christian; Riechelmann, Herbert; Schmutzhard, Joachim; Gottfried, Timo; Dejaco, Daniel; Tauber, Helmuth; Josip, Ena; Henninger, Benjamin
Abstract: Background and Purpose: Diffusion‐weighted imaging(DWI) in MRI has been developed as an important tool for the detection of cholesteatoma. Various DWI sequences are available. This study aims to evaluate the importance of the observer's reliance level for the detection of cholesteatoma. Methods: Forty patients meeting the following criteria were included in the study: (1) chronic otitis media, (2) preoperative MRI including various DWI sequences, and (3) middle‐ear surgery. The MRI protocol contained the following sequences: (1) axial and (2) coronal echoplanar imaging (EPI) readout‐segmented (RESOLVE) DWI with Trace acquisition and (3) coronal non‐EPI half‐Fourier acquired single‐shot turbo spin‐echo (HASTE) DWI. Cholesteatoma diagnosis was based on standard diagnostic criteria for cholesteatoma with DWI. Additionally, the radiologists were asked to grade personal reliance on their diagnosis using a Likert‐type scale from 1 = very insecure to 5 = very secure . Results: Axial and coronal RESOLVE DWI showed a sensitivity of 77.3% and a specificity of 72.2%, respectively. The mean reliance was 3.9 for axial and 3.8 for coronal images. HASTE DWI had a sensitivity/specificity of 81.8%/66.7% with the highest reliance of all evaluated sequences (4.4). Cases with a reliance level of 5 showed a sensitivity/specificity of 100% in all sequences. A reliance level of 5 was given in the axial and coronal RESOLVE DWI in 32.5% of cases and in the HASTE DWI in 57.5%. Conclusion: The evaluated DWI sequences showed comparable results. The reliance level significantly improved the predictor of cholesteatoma disease with MRI techniques.